Energy Transition and Sustainable Development: Economic Constraints and Environmental Incentives - Benamara , Larbi; Basset , Samira (Journal of Ecohumanism, 2025)
The study aims to analyze the complex relationship between energy transition and the achievement of sustainable development, focusing on economic barriers on the one hand and environmental drivers on the other. The shift from fossil fuels to renewable energy has become a strategic and ethical necessity in the face of climate change and the imperative to ensure a secure environmental future. However, this path faces major obstacles, particularly in oil producing countries that heavily rely on oil revenues, which complicates energy transition efforts. The study employs an analytical approach to break down the excessive dependence on fossil fuels, a comparative approach to examine different models of energy transition across countries, and a descriptive method to present the theoretical and conceptual framework. The study concludes that political will, public pressure, and the intensification of environmental disasters constitute essential incentives for transition, despite prevailing economic challenges.